EFFECTS OF NUMERICAL-COGNITION AND EMOTIONAL-FREEDOM TECHNIQUES ON MATHEMATICS ANXIETY AND ACHIEVEMENT AMONG NON-SCIENCE SECONDARY SCHOOL STUDENTS WITH PSEUDO-DYSCALCULIA IN IBADAN (2014)
Anxiety and low achievement in Mathematics are critical challenges facing secondary school students in Nigeria, especially non-science. One of the factors responsible for poor performance in Mathematics is phobia. Many children and young adults develop a fear for Mathematics while they are in school, often as a result of inappropriate methods of teaching or lack of interest on the part of the students. Despite previous studies on Mathematics anxiety (such as systematic desensitization; Verbalizing Fears and Frustrations Techniques; etc.), the problem of Mathematics anxiety and low achievement still persist. Mathematics anxiety and low achievement are both emotional and cognitive problems hence; there is need for Numerical Cognition (NCT) and Emotional Freedom Techniques (EFT). This study, therefore, investigated the effects of NCT and EFT on Mathematics anxiety and achievement among selected secondary schools. The pretest-posttest, control group, quasi-experimental design was adopted. Simple random sampling technique was used to select 120 participants for the study. The participants were randomly assigned to NCT, EFT and control groups. The training was conducted for ten weeks. Mathematics Achievement test (r = 0.90), Mathematics Anxiety scale (α = 0.89), Mathematics Efficacy scale (α = 0.86) and Pseudo-dyscalculia scale (α = 0.93) were used for data collection. Fourteen hypotheses were tested at 0.05 level of significance and data were analysed using Analysis of Covariance. There were significant main effects of treatments on Mathematics anxiety (F(2,109) = 173.020, ŋ2 = 0.760) and achievement F(2,109) = 42.161, ŋ2 = 0.432). The treatments accounted for 83.0% variance in the reduction of Mathematics anxiety of the participants while EFT was more effective (x = 33.8) than NCT (x = 45.4) in reducing students’ Mathematics anxiety. Also, the treatment accounted for 78.6% variance in Mathematics achievement of the participants while EFT was also more effective (x = 71.7) than NCT (x = 59.3) in enhancing students’ Mathematics achievement. There were significant main effects of Mathematics efficacy (F(1,109) = 34.973, ŋ2 = 0.243) on Mathematics anxiety. There were significant interactive effects of treatments and Mathematics efficacy (F(2,109) = 26.394, ŋ = 0.195) on Mathematics anxiety. Also, there were significant main effects of Mathematics efficacy (F(1,109) = 21.00, ŋ2 = 0.162) on Mathematics achievement. There were significant interactive effects of treatments and Mathematics efficacy (F(2,109) = 6.116, ŋ2 = 0.053) on Mathematics achievement of the students. There were 3-way interaction effects of treatments, mathematics efficacy and gender on Mathematics anxiety (F(2,109) = 7.327, ŋ2 = 0.063). By implication, these two techniques are important in helping students to have positive thought about Mathematics and learn how to adjust their negative thought and believe in their ability to excel in the subject. Numerical-cognition and emotional-freedom techniques were effective in reducing anxiety and enhancing achievement in Mathematics in both male and female. Based on these findings, it is recommended that these techniques could resolve phobia in Mathematics and improve the students’ performance in the subject.